Functional fitness test for screening the risk of falls in the elderly: using decision tree technique - Tongterm, Tachapon; Suputtitada, Areerat; Lawsirirat, Chaipat; Janwantanakul, Prawit (Journal of exercise physiology online, 2015)
The aim of this study was to make the Functional Fitness Test for screening the risk of falls in the elderly by using the Decision Tree Technique. Selected by Multistage Random Sampling, we analyzed elderly subjects in 64 districts in 16 provinces in Thailand. The cross-sectional study consisted of 5,632 elderly (of which 1,869 were men and 3,763 were women). The subjects' physical fitness parameters (muscle strength, aerobic endurance, flexibility, and agility/balance) were studied using six different fitness tests: Chair Stand, Arm Curl, Step in Place, Chair Sit-and-Reach, Back Scratch, and the 8 Foot Up and Go. The fall risk parameter assessed was Berg Balance Scale (BBS). The analysis of Functional Fitness Test for screening the risk of falls in the elderly used the Decision Tree Technique algorithm C4.5 (J48). The 8 Foot Up and Go, Chair Stand, and Step in Place predicted the risk of falls in the elderly with accuracy in prediction (Correctly Classified Instances) equal to 95.76%. When using the Berg Balance Scale test as the dependent variable, the BBS was [greater than or equal to] 45 points (meaning, low risk of fall) and when it was <45 points (a high risk of fall) for classifying the risk of falls in the elderly, with Decision Tree Technique model gave information that functional fitness in the 8 Foot Up and Go, Chair Stand, and Step in Place classified the risk of falls in the elderly with level of Correctly Classified Instances equal to 95.76%. Key Words: Functional fitness, Falls, Elderly, Decision tree